2014
DOI: 10.1016/j.ejpal.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential profile in partner aggressors: Prison vs. mandatory community intervention programs

Abstract: In Spain, there are two types of sentence for partner aggressors: prison sentence and the alternative measure, specifically psychosocial intervention programs. The goal of this study was to determine differences in the delinquent and psychopathological profile of these aggressors as a function of the prison sentence received, for which the models proposed by Dutton (1995) and Holtzworth-Munroe and Stuart (1994) were followed. The sample was made up of 50 incarcerated aggressors and 40 men sentenced to mandator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
5
15
0
Order By: Relevance
“…We underline the differences in Minor psychological aggression, in Group LR compared to the other two groups, and in Factor 3, with thoughts justifying violence, between Groups HR and MR, with higher scores in Group MR, coinciding with the group with predominantly antisocial disorder ( Ruiz-Hernández et al, 2015 , Ureña et al, 2015 ). These results imply that the main differences between these aggressors are in the way they resolve conflicts, depending on whether or not they have a personality disorder, and what type of disorder, their level of social maladjustment, and their level of stress ( García-Jiménez et al, 2014 , Loinaz et al, 2012b , Loinaz et al, 2011 ).…”
Section: Discussionmentioning
confidence: 97%
“…We underline the differences in Minor psychological aggression, in Group LR compared to the other two groups, and in Factor 3, with thoughts justifying violence, between Groups HR and MR, with higher scores in Group MR, coinciding with the group with predominantly antisocial disorder ( Ruiz-Hernández et al, 2015 , Ureña et al, 2015 ). These results imply that the main differences between these aggressors are in the way they resolve conflicts, depending on whether or not they have a personality disorder, and what type of disorder, their level of social maladjustment, and their level of stress ( García-Jiménez et al, 2014 , Loinaz et al, 2012b , Loinaz et al, 2011 ).…”
Section: Discussionmentioning
confidence: 97%
“…In fact, there were two murderers among this group of specialist batterers, which challenges the classical notion that the family-only batterer usually presents a low level of partner violence. Specialist and generalist batterers showed no significant differences in other Cluster B characteristics such as histrionic or narcissistic personality that have been related to partner violence (Ehrensaft et al, 2006;García-Jiménez, Godoy-Fernández, Llor-Esteban, & Ruiz-Hernández, 2014;Torres, Lemos-Giráldez, & Herrero, 2013), and batterer treatment efficacy (Novo, Fariña, Seijo, & Arce, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies noted that the risk factors for IPV coincide with the factors proposed in research on common delinquents (García-Jiménez, Godoy-Fernández, Llor-Esteban, & Ruíz-Hernández, 2014). Studies comparing inmates who have committed offenses against intimate partners with other offenders observed that individuals in both groups tend to be similar in terms of their criminal records, violence perpetration outside the family, use of weapons, alcohol and drug use, and experiences with abuse (e.g., Felson & Lane, 2010;Ruíz-Hernández, García-Jiménez, Llor-Esteban, & Godoy-Fernández, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Knowing the characteristics of the IPV perpetrators, as well those who allow to differentiate between incarcerated and nonincarcerated IPV perpetrators, provides a practical and successful method for planning and designing effective interventions with abusive partners (Coulter & VandeWeerd, 2009). The argument that IPV perpetrators are a heterogeneous group, the increasing number of male individuals sentenced for IPV and the legal variations in sentences applied to these offenders supports investigations focused on offenders' profiles (García-Jiménez et al, 2014). Nevertheless, in Portugal, research on IPV perpetrators' characteristics remains scarce.…”
Section: Introductionmentioning
confidence: 99%